Optimal scheduling with dynamic line ratings and intermittent wind power - Banerjee, B.; Jayaweera, D.; Islam, Syed (IEEE Computer Society, 2014)
© 2014 IEEE. Limited transmission capacity may lead to wind curtailment during periods of high availability of wind. This paper presents an improved methodology to quantify the latent scheduling capacity of a power system taking into account stochastic variation in line-thermal rating, intermittency of wind, and mitigating the risk of network congestion associated with high penetration of wind. The approach is aimed at strategic planning of power systems in the context of power systems with short to medium length lines with a priori known unit commitment decisions and uses stochastic optimization with a two stage recourse action. Results suggest that a considerable level of wind penetration is possible with dynamic line ratings, without adversely affecting the risk of network congestion.